The Effectiveness of the Contextual Learning Approach in Improving Students’ Vocabulary Achievement and Retention - Nurul Aidah Majid; Kalsum Kalsum; Zulfah Fakhruddin; Yessicka Noviasmy (JELITA, 2026)
This study aims to investigate the effectiveness of the Contextual Learning Approach in enhancing students’ vocabulary retention at SMP Negeri 10 Parepare. The research employed a pre-experimental design with a one-group pre-test, post-test, and delayed post-test. The sample consisted of 30 eighth-grade students selected through random sampling. The instruments used in this study were vocabulary tests administered in three stages: pre-test, post-test, and delayed post-test. The data were analyzed using descriptive statistics and paired-sample t-test to examine the effectiveness of the treatment. The results of the study showed that the mean score of the students increased from 57.80 in the pre-test to 77.30 in the post-test, and further increased to 89.83 in the delayed post-test. The inferential analysis revealed a significant difference between the pre-test and post-test scores (t = -5.215, p < 0.05). In addition, the delayed post-test results indicated that students were able to retain the vocabulary learned during the treatment period. Therefore, the findings suggest that the Contextual Learning Approach may contribute to improving students’ vocabulary achievement and retention.